1R2T-1R Type Rope-driven Lower Limb Rehabilitation Robot Kinematics and Its Workspace - Wang Zhijun; Wang Junpeng (Jixie chuandong)
For patients with lower limb motor hemiplegia, a 1R2T-1R type rope-driven lower limb rehabilitation robot is proposed and its complete model is built based on human lower limb movement patterns. The kinematic forward and inverse solution analysis is carried out for this robot and its correctness is verified. Based on the Monte Carlo method, the controllable workspace and the actual workspace of this robot under the premise of force closure are solved in the Matlab environment and compared. The results show that the rehabilitation robot has a reasonable configuration and its working range can meet the needs of patients' rehabilitation training, which provides some reference for subsequent parameter optimization and trajectory planning.